Treadmill versus overground gait training in patients with lower limb burn injury: A matched control study. Issue 1 (February 2022) - Özkal, Özden; Kısmet, Kemal; Konan, Ali; Hayran, Mutlu; Topuz, Semra
Highlights: Gait parameters and functional mobility are adversely affected by lower extremity burns. Gait training should be added to early rehabilitation programs for lower limb burns. Both overground and treadmill gait training are effective tools to improve gait symmetry and functional mobility. Abstract: Introduction: Gait impairment is commonly seen in patients with a lower limb burn injury (LLBI). Therefore, the aim of this study was to investigate the effects of two different gait training modes on gait symmetry, functional mobility and kinesiophobia in patients with LLBI. Methods: This matched control study was conducted between January 2017 and August 2018. Patients with LLBI ( n = 28) were allocated to 2 different groups by matching according to burn localization, age, and gender. Group 1 (overground group: n = 14) received overground gait training in addition to standard burn rehabilitation, and Group 2 (treadmill group: n = 14) received treadmill gait training in addition to standard burn rehabilitation. The rehabilitation program and gait training were started when the patient was admitted to the hospital and ended on discharge. These physical therapy interventions were performed 5 days per week. The gait training intensity, including walking speed and duration, was determined according to patient tolerance. Gait parameters, functional mobility, kinesiophobia and pain values were evaluated with GAITRite, the timed up-and-go test (TUG), Tampa Kinesiophobia Scale and Visual Analogue Scale, respectively. These evaluations were made twice; on admission and immediately prior to discharge. Gait symmetry was calculated using the Symmetry Index. Results: The baseline characteristics of the groups and initial outcome values were similar. In the comparison of the differences between the overground and treadmill groups, the change in kinesiophobia and TUG values were significantly higher in the treadmill group ( p = 0.01, p = 0.02, respectively). The intragroup comparisons showed significant differences in SI in respect of step length ( p = 0.004), swing ( p = 0.006), stance ( p = 0.008) and velocity ( p = 0.001), cadence ( p = 0.001), TUG ( p = 0.001), kinesiophobia ( p = 0.001) and pain ( p = 0.001) in the overground group. Statistically significant differences were determined in step length ( p = 0.01), swing ( p = 0.01), stance ( p = 0.02) and velocity ( p = 0.001), cadence ( p = 0.001), TUG ( p = 0.001), kinesiophobia ( p = 0.001) and pain ( p = 0.001) in the treadmill group, when pre and post-training values were compared. Conclusions: The results of this study have shown that treadmill gait training was more effective in the improvement of functional mobility and reduction in kinesiophobia levels of patients with LLBI compared to overground gait training. Both overground and treadmill gait training also provide greater improvements in the velocity and cadence, and gait symmetry for step length, swing and stance in patients with LLBI. Clinical trial registration number: NCT03217526.